Effects of Functional Strategies on Service Delivery in Meru County Government, Kenya - Murithi, Olivia Gakii; Obuba, Robert (International Journal of Business, Economics, and Social Development, 2024)
The Meru County government had devised functional strategies; however, their execution had been lacking, resulting in unsatisfactory service delivery. Moreover, funds in Meru County had been redirected to unauthorized expenditures, with the government unable to provide documentation for a spending amounting to Sh209 million in the 2021/2022 fiscal year. Challenges faced by the County government extended to limited financial resources and instances of fund misappropriation. The study aimed to explore the effects of functional strategies on service delivery in Meru County Government. The theoretical foundation of the study incorporated ideas from Strategic Fit Theory. To carry out the research, an explanatory research design was employed. Both primary and secondary data was utilized, with primary data collected through the use of semi-structured questionnaires. A pilot test was carried out in the Embu County government to reveal the reliability and validity of the research instrument. Qualitative data analysis employed thematic analysis, presenting the results in a narrative format. For quantitative data, both descriptive and inferential statistics were utilized. Descriptive statistics encompassed frequency distribution, mean (indicating central tendency), standard deviation (measuring dispersion), and percentages. Inferential statistics involved Pearson correlation analysis and multivariate regression analysis. The study found that Functional strategies account for 83.0% of the performance in Meru County Government. The study recommends that county governments should develop policies to ensure effective control of county activities and enhance staff supervision across various departments.